VMware vSphere design essentials : unleash the performance, availability, and workload efficiency of your virtual data center using this fast-paced guide /: unleash the performance, availability, and workload efficiency of your virtual data center using this fast-paced guide. (2015) - Udayakumar, Puthiyavan
No abstract available